2017
DOI: 10.1242/dev.156224
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin organization at the nuclear periphery as revealed by image analysis of structured illumination microscopy data

Abstract: The nuclear periphery (NP) plays a substantial role in chromatin organization. Heterochromatin at the NP is interspersed with active chromatin surrounding nuclear pore complexes (NPCs); however, details of the peripheral chromatin organization are missing. To discern the distribution of epigenetic marks at the NP of HeLa nuclei, we used structured illumination microscopy combined with a new MATLAB software tool for automatic NP and NPC detection, measurements of fluorescent intensity and statistical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our research showed that the PCL2 gene upregulated H3K4me2 and down-regulated H3K9me2, which does not seem to explain that these two changes are directly related to cell proliferation. But studies have shown that in specific cell cycles, the modification of H3K4me2 and H3K9me2 is related to chromatin inhibition [34]. Therefore, the mechanism that PCL2 alters the methylation of histone sites and the changes in cell fate caused by changes in these histone sites will be our future investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Our research showed that the PCL2 gene upregulated H3K4me2 and down-regulated H3K9me2, which does not seem to explain that these two changes are directly related to cell proliferation. But studies have shown that in specific cell cycles, the modification of H3K4me2 and H3K9me2 is related to chromatin inhibition [34]. Therefore, the mechanism that PCL2 alters the methylation of histone sites and the changes in cell fate caused by changes in these histone sites will be our future investigation.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that nuclear periphery is enriched in condensed heterochromatin, justifies the association of H3K9me3 marks in K97E aggregates. Though lamins at the periphery are known to recruit condensed heterochromatin [57] however, reports have mentioned the existence histone marks for active chromatin near the nuclear pore complexes (NPC) [58].…”
Section: Discussionmentioning
confidence: 99%
“…Euchromatin is generally less condensed, rich in GC content and histone modifications indicative of active transcription, such as H3K4me3, H3K27ac, H4K8ac and H4K16ac (Lawrence et al, 2016). Genomic regions embedded in euchromatin tend to be positioned centrally in the nucleus, apart from nuclear pore regions (Fišerová et al, 2017) located at the nuclear membrane. In contrast, heterochromatin is more compacted, thereby less accessible, largely transcriptionally inactive and decorated with H3K9me3 (facultative heterochromatin) and H3K27me3 (constitutive heterochromatin) histone marks (Penagos-Puig & Furlan-Magaril, 2020).…”
Section: Table Of Contents Introductionmentioning
confidence: 99%